Effects of Two Reflective Teaching Strategies on Secondary School Teachers’ Classroom Practices and Students’ Achievement in Biology in Ibadan (2014)
The teaching of biology has always been beset by routine and inadequate classroom practices and poor students‟ achievement. Most of the methods adopted in teaching the subject did not bring about improved teachers‟ classroom practices even where they affected students‟ performance. This is partly because of the inability of biology teachers to carry out reflective teaching which involves continuously examining and evaluating their classroom practices. Reflective teaching strategies have been found to have the potential to improve teachers‟ professional practice. Previous studies on biology teaching and learning in Nigeria have concentrated more on instructional methods used by teachers than on the use of instructional process to improve students‟ achievements. This study, therefore, determined the effect of Reflective Focus Group Discussion - RFGD and Reflective Peer Observation - RPO strategies on teachers‟ classroom practices and students‟ achievement in biology. It also considered the moderating effects of teachers‟ reflective teaching knowledge and gender. The study adopted a pretest-posttest, control group, quasi-experimental design using a 3x2x2 factorial matrix. Eighteen Senior School II biology teachers and intact classes of 576 students in all were drawn from nine selected secondary schools in Ibadan metropolis. The schools were randomly assigned to experimental and control groups. The two experimental groups were exposed to RFGD and RPO strategies respectively while the control group was exposed to conventional method. The treatment lasted for eight weeks. Instruments used were: Teachers‟ Instructional Guide for RFGD strategy (r = 0.82), Teachers‟ Instructional Guide for RPO strategy (r=0.80), Teachers‟ Classroom Practice Observation Scale (r = 0.80), Teachers Instructional Guide for Conventional Method (r = 0.85), Instructional Guide for Facilitator (r = 0.72), Instructional Guide for Observers (r = 0.70), Reflective Teaching Knowledge Test (r = 0.85) and Students‟ Achievement Test in Biology (r = 0.86). Seven hypotheses were tested at the 0.05 level of significance. Data were analysed using descriptive statistics, Analysis of Covariance (ANCOVA) and Scheffe post hoc test. Treatment had significant effects on teachers‟ classroom practices (F(2,17)=148.3; 2=0.81) and students‟ achievement (F(2,563)=218.5; 2=0.49). Teachers in the RFGD group had highest classroom practices score (x=83.7) followed by RPO (x=76.9) while the control had the least ( x =31.3). Students of teachers in the RFGD group had the highest achievement mean score ( x =14.8) followed by those in RPO group ( x =12.2) and control group ( x =9.3). Teachers‟ reflective teaching knowledge and gender had no significant effect on teachers‟ classroom practices and students‟ achievement. Interaction effect of treatment and teachers‟ gender was significant on students‟ achievement (F(2,563) = 5.4; 2=0.12) with RFGD being more effective for both genders while others were not significant on teachers‟ classroom practices and students‟ achievement. Interaction effects of treatment, teachers‟ gender and reflective knowledge was not significant on teachers‟ classroom practices and students‟ achievement. Reflective focus group discussion followed by reflective peer observation strategies improved teachers‟ classroom practices and students‟ achievement in biology. Therefore, the two strategies should be used by biology teachers for improved classroom practices